Genomic‐based epidemiology reveals independent origins and gene flow of glyphosate resistance in Bassia scoparia populations across North America. Issue 21 (21st October 2021) - Ravet, Karl; Sparks, Crystal D.; Dixon, Andrea L.; Küpper, Anita; Westra, Eric P.; Pettinga, Dean J.; Tranel, Patrick J.; Felix, Joel; Morishita, Don W.; Jha, Prashant; Kniss, Andrew; Stahlman, Phillip W.; et al.
Abstract: Genomic‐based epidemiology can provide insight into the origins and spread of herbicide resistance mechanisms in weeds. We used kochia ( Bassia scoparia ) populations resistant to the herbicide glyphosate from across western North America to test the alternative hypotheses that (i) a single EPSPS gene duplication event occurred initially in the Central Great Plains and then subsequently spread to all other geographical areas now exhibiting glyphosate‐resistant kochia populations or that (ii) gene duplication occurred multiple times in independent events in a case of parallel evolution. We used qPCR markers previously developed for measuring the structure of the EPSPS tandem duplication to investigate whether all glyphosate‐resistant individuals had the same EPSPS repeat structure. We also investigated population structure using simple sequence repeat markers to determine the relatedness of kochia populations from across the Central Great Plains, Northern Plains and the Pacific Northwest. We found that the original EPSPS duplication genotype was predominant in the Central Great Plains where glyphosate resistance was first reported. We identified two additional EPSPS duplication genotypes, one having geographical associations with the Northern Plains and the other with the Pacific Northwest. The EPSPS duplication genotype from the Pacific Northwest seems likely to represent a second, independent evolutionary origin of a resistance allele. We found evidence of gene flow across populations and a general lack of population structure. The results support at least two independent evolutionary origins of glyphosate resistance in kochia, followed by substantial and mostly geographically localized gene flow to spread the resistance alleles into diverse genetic backgrounds.